Rediscovery and redescription of Tetranychus gigas (Acari, Prostigmata, Tetranychidae) - Návia, Denise; Flechtmann, Carlos H.w. (Zootaxa, 2004)
Tetranychus gigas Pritchard & Baker, 1955 is redescribed from paratypes and from Brazilian specimens collected from soybean.